Utilización de materiales didácticos para el desarrollo de la psicomotricidad en los niños 4 años de la Unidad Educativa Dr. Lorenzo Rufo Peña - Muñoz Posligua, Adriana Judith (2023)
The present research work focuses on teaching materials for the development of psychomotor skills in 4-year-old children of the “Dr. Lorenzo Rufo Peña” from the city of Vinces. Different children enter school education who lack good control over their hands when carrying out some activity, therefore, it is necessary for the teacher to determine the necessary resources for the full development of the child. It is important that the family environment encourages the use of materials that help the development of their motor skills. Therefore, this case study focuses on descriptive and field research types, to analyze everything about the teaching materials and thus obtain application data from both teachers and parents.